2020
DOI: 10.1186/s12870-020-02598-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of miRNAs related to sexual differentiation of strobili in Ginkgo biloba by integration analysis of small RNA, RNA, and degradome sequencing

Abstract: Background: Ginkgo biloba, a typical dioecious plant, is a traditional medicinal plant widely planted. However, it has a long juvenile period, which severely affected the breeding and cultivation of superior ginkgo varieties. Results: In order to clarify the complex mechanism of sexual differentiation in G. biloba strobili. Here, a total of 3293 miRNAs were identified in buds and strobili of G. biloba, including 1085 known miRNAs and 2208 novel miRNAs using the three sequencing approaches of transcriptome, sma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…analysis, miRNA targets pred. Liu et al ( 2020b ) Gossypium hirsutum sRNA-seq Abdurakhmonov et al ( 2008 ) Gossypium hirsutum sRNA-seq, miRNA analysis and targets pred. Pang et al 2009 ) Gossypium hirsutum sRNA-seq, degrad.…”
Section: Role Of Small Rnas In Apomictic Ovulesmentioning
confidence: 99%
“…analysis, miRNA targets pred. Liu et al ( 2020b ) Gossypium hirsutum sRNA-seq Abdurakhmonov et al ( 2008 ) Gossypium hirsutum sRNA-seq, miRNA analysis and targets pred. Pang et al 2009 ) Gossypium hirsutum sRNA-seq, degrad.…”
Section: Role Of Small Rnas In Apomictic Ovulesmentioning
confidence: 99%
“… 6 , 7 Besides, Liu et al confirmed that CYC is recent and originated from CIN in angiosperms while G. biloba belong to ancient gymnosperms. 54 , 55 Therefore, we speculated that the difference in evolutionary time may cause this result. In addition, GbTCP09-12 was found to distribute in the same chromosome and adjacent to each other.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA has a complex regulatory network in cells, which can regulate the expression of many genes through a miRNA and the expression of a specific gene by the combination of several miRNAs (Liu et al 2020). miRNAs have the characteristic of being highly matched with target genes, having strong targeting preference for transcription factors or other genes controlling development, and high diversity of species.…”
Section: Biological Functions Of Plant Mirnasmentioning
confidence: 99%
“…microRNA (miRNA) is a form of single-strand endogenous RNA with a length of 20-25 nt. It does not have a coding region and is highly conservative, tissue specific and stage specific (Du et al 2018;Liu et al 2020). The main function of miRNA is to downregulate the expression of target genes at the post-transcriptional level through translation suppression, as well as to target mRNA cleavage and epigenetic modification (Bartel 2004;Yu et al 2015).…”
Section: Introductionmentioning
confidence: 99%